2002
DOI: 10.1089/105072502320288483
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Thyroid Autoimmunity and Yersinia Enterocolitica Antibodies

Abstract: It has previously been proposed that subclinical Yersinia enterocolitica infection may play a role in autoimmune thyroid disease (AITD). In this study, we investigated the relationship between the thyroid autoantibodies and the antibodies that produced against different serotypes of Y. enterocolitica. A total of 215 subjects were included into the study (65 newly diagnosed Graves' disease [GD], 57 Hashimoto's thyroiditis [HT], 53 nontoxic diffuse goiter [NTDG], and 40 subjects for control group [CG]). Thyroid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 10 publications
0
23
0
Order By: Relevance
“…In Greece, 25% of Hashimoto patients had IgG antibodies and 2.8% had IgA antibodies, compared with 2 and 0% respectively in controls (196). A higher incidence of Y. enterocolitica antibodies in Graves and Hashimoto patients than in controls was also found in Japan and Turkey (197,198). However, there are also studies that could not confirm these findings and found a similar rate of seropositivity in AITD patients and controls (199,200).…”
Section: Y Enterocolitica Infectionmentioning
confidence: 98%
“…In Greece, 25% of Hashimoto patients had IgG antibodies and 2.8% had IgA antibodies, compared with 2 and 0% respectively in controls (196). A higher incidence of Y. enterocolitica antibodies in Graves and Hashimoto patients than in controls was also found in Japan and Turkey (197,198). However, there are also studies that could not confirm these findings and found a similar rate of seropositivity in AITD patients and controls (199,200).…”
Section: Y Enterocolitica Infectionmentioning
confidence: 98%
“…Both genetic predisposition and cross-reactivity between antigens have been hypothesized as potential mechanisms for this association. A functional polymorphism in the protein tyrosine phosphatase gene, the PTPN22 620W allele has been recognized as a predisposing factor for several autoimmune disorders, including AITD, Wegener’s granulomatosis, and ANCA positivity (5456). PTPN22 is located on chromosome 1p13.3–13.1.10 and encodes an 807-amino acid protein that interacts with Csk, a tyrosine kinase that is involved in the intracellular signaling cascade following T-cell activation.…”
Section: Glomerular Disease Related To Aitmentioning
confidence: 99%
“…Its success in treating CDI sparked interest in investigating FMT as a treatment for other medical conditions associated with intestinal dysbiosis, such as ulcerative colitis [911], Crohn’s disease (CD) [1214], irritable bowel syndrome (IBS) [15, 16], and others, including metabolic syndrome [17], neurodevelopmental [18], and autoimmune disorders [19]. Despite the excitement due to its therapeutic potential, FMT also presents challenges for researchers and clinicians with potential adverse outcomes, including the transfer of infectious organisms [20] or contaminants from the environment [21, 22].…”
Section: Introductionmentioning
confidence: 99%